2010
DOI: 10.1074/jbc.m110.119255
|View full text |Cite
|
Sign up to set email alerts
|

PfSRPK1, a Novel Splicing-related Kinase from Plasmodium falciparum

Abstract: Even though it is increasingly evident that post-transcriptional events like mRNA processing and splicing may regulate gene expression and proteome diversity of malaria parasite Plasmodium, molecular mechanisms that regulate events like mRNA splicing in malaria parasite are poorly understood. Protein kinases control a wide variety of cellular events in almost all eukaryotes, including modulation of mRNA splicing, transport, and stability. We have identified a novel splicing-related protein kinase from Plasmodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…The gene product SRPK1 catalyzes phosphorylation of the parasite PfSR1 (Ser/Arg-rich) protein, involved in mRNA splicing in the nucleus23. The SRPK1 gene transcript is expressed in P. falciparum asexual stages and at an even higher level in gametocytes24, and its orthologue is necessary for male gamete maturation in rodent malaria parasites25.…”
Section: Discussionmentioning
confidence: 99%
“…The gene product SRPK1 catalyzes phosphorylation of the parasite PfSR1 (Ser/Arg-rich) protein, involved in mRNA splicing in the nucleus23. The SRPK1 gene transcript is expressed in P. falciparum asexual stages and at an even higher level in gametocytes24, and its orthologue is necessary for male gamete maturation in rodent malaria parasites25.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, and as shown by reverse genetics, these two enzymes are necessary for completion of the parasite's asexual replication cycle. Dixit et al also showed that PfCLK4 (which they refer to as PfSRPK1) inhibits mRNA splicing by phosphorylating PfSR1, a putative splicing factor known to interact with RNA [82].…”
Section: The Cmgc Group and Other Cell Cycle Control Kinasesmentioning
confidence: 99%
“…Apicomplexa parasites also encode this capacity with an exceptional expansion of the RRM-domain family (1% of total genes) that includes conserved SR and hnRNP proteins [29]. Despite the abundance of RNA-binding proteins and potential importance to parasite biology there has been limited research on these factors (TgDRE1 [23, 47]; PfSR1 [48, 49]). Alternative splicing is regulated by phosphorylation of the SR factors by cdc2-like kinases (CLK) of the CMGC family.…”
Section: Regulation Of the Alternative Mrna Splicingmentioning
confidence: 99%
“…Alternative splicing is regulated by phosphorylation of the SR factors by cdc2-like kinases (CLK) of the CMGC family. Apicomplexa genomes encode four members of CLK kinase family [48, 50]. Given the homolog of PfCLK-1/Lammer and PfCLK-2 kinases to yeast splicing kinase Sky1p it was expected these kinases would have a role in alternate splicing.…”
Section: Regulation Of the Alternative Mrna Splicingmentioning
confidence: 99%
See 1 more Smart Citation